Decoration of vertical graphene with aerosol nanoparticles for gas sensing. (22nd July 2015) - Cui, Shumao; Guo, Xiaoru; Ren, Ren; Zhou, Guihua; Chen, Junhong
Abstract: A facile method was demonstrated to decorate aerosol Ag nanoparticles onto vertical graphene surfaces using a mini-arc plasma reactor. The vertical graphene was directly grown on a sensor electrode using a plasma-enhanced chemical vapor deposition (PECVD) method. The aerosol Ag nanoparticles were synthesized by a simple vapor condensation process using a mini-arc plasma source. Then, the nanoparticles were assembled on the surface of vertical graphene through the assistance of an electric field. Based on our observation, nonagglomerated Ag nanoparticles formed in the gas phase and were assembled onto vertical graphene sheets. Nanohybrids of Ag nanoparticle-decorated vertical graphene were characterized for ammonia gas detection at room temperature. The vertical graphene served as the conductance channel, and the conductance change upon exposure to ammonia was used as the sensing signal. The sensing results show that Ag nanoparticles significantly improve the sensitivity, response time, and recovery time of the sensor.